NUMERICAL MODELING OF STEEL FLOW IN A MULTI-STRAND CONTINUOUS CASTING TUNDISH - Marek Warzecha (Acta Metallurgica Slovaca, 2014)
The tundish is an important unit in a continuous casting device. The flow of the liquid steel in tundishes has a crucial influence on quality of steel, which is nowadays defined by the number and size of non-metallic inclusions. In order to improve the process of removal of inclusions from liquid steel, investigations are being made worldwide to obtain the most favourable shape of the tundish working space to control the flow. The main purpose of research presented in this paper was to analyze the liquid steel flow structure and temperature distribution in the investigated continuous casting tundish. Numerical simulations of liquid steel flow through the tundish were carried out using commercial computational fluid dynamics (CFD) software AnsysFluent. The results of numerical simulation allow to diagnose the tundish with currently working configuration.